Energy Consumption Optimisation for Duty-Cycled Schemes in Shadowed Environments. (28th May 2014) - Predojev, Tatjana; Alonso-Zarate, Jesus; Dohler, Mischa; Alonso, Luis
The focus of this study is the optimal configuration of a wireless low-power duty-cycled network with respect to the minimal energy consumption. Precisely, the energy consumption of a truncated-ARQ scheme in realistic shadowing environments is examined for the reference IEEE 802.15.4e standard protocol and for its cooperative extension that is presented in the paper. We show how to choose between the direct or multihop forwarding and the cooperative version of the two. We determine the optimal forwarding strategy for both loose and strict reliability requirements. Low-power links are parametrised by the interdevice distance and the corresponding outage probability, for the fixed output transmission power. It is shown that significant amounts of energy can be saved when the most adequate scheme of the three is applied. All analytical results are validated in the network simulator ns-3.